Intelligent Triage Assistant - Duangdee, Wannarat; Lalitrojwong, Pattarachai (My University, 2021)
The triage of outpatient department is a vital process to screen patients. In addition, assessing the emergency case by the outpatient department can determine the quality of service. In emergency case, the patients have to be treated as soon as they arrive. If the triage of this case is delayed and the patients have major symptoms, it may develop serious complications leading to the cause of death or disability. Accordingly, assessing and making triage decisions, and assigning the level of patient acuity require being accurate, rapid and trustworthy in order to take care and treat them in time. Due to the fact that nowadays there is only one nurse on duty for the triage, he or she cannot well handle a bunch of patients arriving for treatment. According to Hospital and Healthcare Standards, 4th edition, the Healthcare Accreditation Institute (Public Organization) allows the use of technology to improve hospital services. This research aims to develop an intelligent triage assistant. To help the process by making triage decisions for all the patients promptly, assigning an acuity level and screening and assigning the patients to an area based on acuity. If unsuitable results happen, the triage nurse can be on duty promptly. Our intelligent triage assistant has been implemented using Visual Studio C#, Microsoft SQL Server for the database, and QnA Maker for the knowledge base. The application has been tested by outpatient nurses. They are quite satisfied with the primary outcome and recommend further improvements for future work.
Keywords: Chatbot; Expert system; Knowledge base; Outpatient; Triage